2021
DOI: 10.1101/2021.01.21.427382
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Targeted sensors for glutamatergic neurotransmission

Abstract: Optical report of neurotransmitter release allows visualization of excitatory synaptic transmission. Sensitive genetically-encoded glutamate reporters operating with a range of affinities and emission wavelengths are available. However, without targeting to synapses, the specificity of the fluorescent signal is uncertain, compared to sensors directed at vesicles or other synaptic markers. We fused the state-of-the-art reporter iGluSnFR to glutamate receptor auxiliary proteins in order to target it to postsynap… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 58 publications
1
4
0
Order By: Relevance
“…This enables more quantitative measurements of glutamate release over space and time that were previously confounded by saturation effects. Similar advantages were recently demonstrated for another novel variant in culture (13). Secondly, we demonstrated reliable detection of glutamate release associated with electrophysiologically-identified APs in vivo (Figure 5a-g).…”
Section: Discussionsupporting
confidence: 82%
See 4 more Smart Citations
“…This enables more quantitative measurements of glutamate release over space and time that were previously confounded by saturation effects. Similar advantages were recently demonstrated for another novel variant in culture (13). Secondly, we demonstrated reliable detection of glutamate release associated with electrophysiologically-identified APs in vivo (Figure 5a-g).…”
Section: Discussionsupporting
confidence: 82%
“…The spatial specificity of glutamate transmission relies on nanoscopic localization of receptors to post-synaptic densities apposed to presynaptic active zones. However, electrophysiological and imaging studies have suggested that iGluSnFR may be excluded from the post-synaptic density, impacting the indicator's ability to report synaptic transmission when expressed post-synaptically (13). We therefore compared a variety of surface display sequences for their performance at reporting synaptic signals, using the amplitude, SNR, and detection rate of optical minis as readouts.…”
Section: Display Constructs That Improve Optical Mini Signals and Nan...mentioning
confidence: 99%
See 3 more Smart Citations